EasyLiving: Technologies for Intelligent Environments - Brumitt, Barry; Meyers, Brian; Krumm, John; Kern, Amanda; Shafer, Steven (Second International Symposium on Handheld and Ubiqitous Computing (HUC 2000), Bristol, UK, 2000)
The EasyLiving project is concerned with development of an architecture and technologies for intelligent environments which allow the dynamic aggregation of diverse I/O devices into a single coherent user experience. Components of such a system include middleware (to facilitate distributed computing), world modelling (to provide location-based context), perception (to collect information about world state), and service description (to support decomposition of device control, internal logic, and user interface). This paper describes the current research in each of these areas, highlighting some common requirements for any intelligent environment.